Construction and application of two intrinsic models for Ti-Al composite plates considering current parameters - Tao Huang; Yihan Zhai; Binghui Xing; Chaomin Zhang; Nan Xiang; Kexing Song; Wenjing Zhang; Lei Shi (Materials Research Express)
Electroplastic effects present in the electrically assisted (EA) forming process can reduce flow stresses and improve the forming properties of metallic materials. The construction of an intrinsic model is important for the analysis and optimization of the deformation process. This study, therefore, has presented an intrinsic model for the heterogeneous layers of Ti–Al composite plates, incorporating temperature and current parameters. This model is designed to forecast the flow stresses within these heterogeneous layers during EA forming. By employing ABAQUS finite element software, we conducted a finite element analysis of the EA forming process. A modified heterogeneous layer ontology model for Ti-Al composite plates was used in this process. We compared the stress–strain curves obtained from the experimental data with those simulated by our model and conducted a thorough error analysis. The findings indicate that our model, with an R value of 0.9910, an AARE of 3.79%, and an RMSE of 6.55, provides a highly accurate prediction of flow stresses during the EA forming of Ti-Al composite plates. This work is also highly important for optimizing the current-assisted forming process and improving the forming quality and efficiency of Ti-Al composite plate components.